ABSTRACT EXPRESSIONISM: TYPICALLY NORTH AMERICAN - Castellanos, Polo (Archipielago. Revista cultural de nuestra América, 2010)
The Mexican visual artist Polo Castellanos unveils in this work one of the most important schools of modern art, North American abstract expressionism. At the end of the Second World War, the United States was able to insert itself onto the world cultural map with its own art form and culture, which authenticated the "democracy" of Capitalism. Starting with a critical review of its history background, the author reveals the role played by the CIA in encouraging this art form, which expressed anticommunist ideologies and, when not figurative, could not express itself politically.